2022
DOI: 10.1101/2022.09.15.22279948
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential contagiousness of respiratory disease across the United States

Abstract: The initial contagiousness of a communicable disease within a given population is quantified by the basic reproduction number, denoted R_0. The value of R_0 gives the expected number of new cases generated by an infectious person in a wholly susceptible population and depends on both pathogen and population properties. On the basis of compartmental models that reproduce Coronavirus Disease 2019 (COVID-19) surveillance data, we estimated region-specific R_0 values for 280 of 384 metropolitan statistical areas (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 16 publications
(33 reference statements)
2
5
0
Order By: Relevance
“…In earlier work, we demonstrated that new COVID-19 case detection over various periods in 2020 can be faithfully reproduced for 280 (out of the 384) metropolitan statistical areas (MSAs) in the US and all 50 states by region-specific parameterizations of a compartmental model that accounts for time-varying non-pharmaceutical interventions [57]. However, in 2021, the model lost its ability to capture disease transmission dynamics, presumably because of the impacts of vaccination and the emergence of more transmissible SARS-CoV-2 variants, namely, Alpha and Delta.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In earlier work, we demonstrated that new COVID-19 case detection over various periods in 2020 can be faithfully reproduced for 280 (out of the 384) metropolitan statistical areas (MSAs) in the US and all 50 states by region-specific parameterizations of a compartmental model that accounts for time-varying non-pharmaceutical interventions [57]. However, in 2021, the model lost its ability to capture disease transmission dynamics, presumably because of the impacts of vaccination and the emergence of more transmissible SARS-CoV-2 variants, namely, Alpha and Delta.…”
Section: Resultsmentioning
confidence: 99%
“…We determined the intervals of the step functions Y θ ( t ), P τ ( t ), and Λ τ ( t ) (i.e., θ and τ ) using a model-selection procedure described in the Appendix. Simulations and Bayesian inferences were performed as previously described [57] and in the Appendix. Files needed to reproduce inferences using the software package PyBioNetFit [28] are available online (https://github.com/lanl/PyBNF/tree/master/examples/Vax_and_Variants).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each phase is associated with three parameters: an onset time, a sum of rate constants that defines a timescale for transition to a setpoint level of adoption of disease-avoiding behaviors, and the setpoint (the fraction of the regional population adopting disease-avoiding behaviors). We have previously shown that this model is able to reproduce the dynamics of regional COVID-19 epidemics in 2020 in 280 of 384 MSAs in the US [8], including the 15 most populous metropolitan areas [7], and in all 50 states [9]. We adopted a Bayesian inference approach enabled by Markov chain Monte Carlo (MCMC) sampling to obtain samples of region-specific parameter posteriors.…”
Section: Introductionmentioning
confidence: 99%